2018
DOI: 10.1111/bph.14341
|View full text |Cite
|
Sign up to set email alerts
|

The selective mineralocorticoid receptor antagonist eplerenone prevents decompensation of the liver in cirrhosis

Abstract: We showed for the first time that hypoxia leads to a pathogenetic ligand-independent activation of hepatic MRs during cirrhosis resulting in their nuclear translocation and transcriptional activation of the NF-κB pathway. Treatment with eplerenone prevented the worsening of cirrhosis by blocking this ligand-independent activation of the MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…It is possible that there are cell type‐specific effects on MR expression, as in mice fed with a choline‐deficient and amino‐acid defined (CDAA) diet, an increase in MR mRNA was observed in HSCs but a reduction in hepatocytes (Pizarro et al, 2015). We also observed a reduction of MR mRNA content in freshly isolated hepatocytes from rats with decompensated liver cirrhosis (Schreier et al, 2018). If this reduced mRNA content is due to reduced transcription or enhanced mRNA degradation is still under investigation, as well as the underlying molecular pathways.…”
Section: Function Of the Mineralocorticoid Receptor And Aldosterone I...supporting
confidence: 55%
See 1 more Smart Citation
“…It is possible that there are cell type‐specific effects on MR expression, as in mice fed with a choline‐deficient and amino‐acid defined (CDAA) diet, an increase in MR mRNA was observed in HSCs but a reduction in hepatocytes (Pizarro et al, 2015). We also observed a reduction of MR mRNA content in freshly isolated hepatocytes from rats with decompensated liver cirrhosis (Schreier et al, 2018). If this reduced mRNA content is due to reduced transcription or enhanced mRNA degradation is still under investigation, as well as the underlying molecular pathways.…”
Section: Function Of the Mineralocorticoid Receptor And Aldosterone I...supporting
confidence: 55%
“…Progression of liver dysfunction depends on the crosstalk of the different cell types within the liver but, while there is evidence that inhibition of the MR is beneficial for liver function (see below), little is known about the cellular mechanisms leading to this effect. In healthy rat livers, the main cell type expressing MRs, at mRNA and protein levels, is the hepatocytes (Schreier et al, 2018), although there are also MRs detectable in LSECs and Kupffer cells (Pizarro et al, 2015). At the moment, it is not clear if rat HSCs also express MRs, as we could detect the appropriate mRNA but not the protein (Schreier et al, 2018).…”
Section: Function Of the Mineralocorticoid Receptor And Aldosterone I...mentioning
confidence: 99%
“…In recent years, many studies have found that NR3C2 serves as a tumor suppressor in many cancers, including hepatocellular carcinoma ( Nie et al, 2015 ; Yang et al, 2019 ). Although NR3C2 status in ACLF has not been explored, MR mRNA and protein expression were reduced in the hepatocytes of patients with cirrhosis and ascites ( Schreier et al, 2018 ). In HBV-ACLF patients, we found that NR3C2 expression was significantly lower among both those with a poor prognosis and those with ACLF-3 grade disease.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of mineralocorticoid receptor expression in the liver against the background of IRP causes pro-inflammatory and profibrotic effects. It was discovered that an increase in the mRNA level in the liver significantly correlates with the expression of pro-inflammatory and profibrotic genes, while use of a specific mineralocorticoid receptor blocker, eplerenone, weakens these effects [15,16]. Our study has demonstrated that in rats, characterized by the low resistance to hypoxia, the vectors of fluctuations in the corticosterone concentrations, as well as in the numbers of its target receptors, were multidirectional on day 3 after the IRP: an increase in the corticosteroid level was accompanied by a reduction in the mineralocorticoid content.…”
Section: Discussionmentioning
confidence: 99%